PENYULUHAN DAN PENDAMPINGAN USAHATANI HIDROPONIK KANGKUNG - Safrin Edy; Bahtiar Hamar; Ismail Failu; Arfandi Arfandi (JICS : Journal Of International Community Service, 2025)
Water spinach (Ipomoea aquatica) is a fast-growing leafy vegetable with high nutritional value, making it a potential source of local food and a means to increase household income. This community service was conducted by the lecturers of the Faculty of Agriculture, Universitas Muhammadiyah Buton, together with students, aiming to enhance the technical and managerial capacity of the community in hydroponic water spinach cultivation in Desa Karae. The implement tation method applied a participatory approach through Participatory Rural Appraisal (PRA), interactive extension, technical demonstra tions, and continuous mentoring. Observations revealed that the rocky and less fertile land conditions can be addressed using a simple hydroponic system based on PVC/net pot and rockwool media. This holistic and participatory approach improved community knowledge, skills, and awareness in utilizing home gardens as food and income sources while promoting self-reliance and the replication of hydroponic farming independently.